Effects of the Sport Education Model on Content Knowledge, Technical Skill, and Game Performance Among Students: A Systematic Review and Meta-Analysis - Hucheng Ma; Zhang Junlong; Zelin Su (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The Sport Education Model (SEM) has emerged as a promising approach for enhancing content comprehension, technical proficiency, and game performance in educational settings. This systematic review and meta-analysis synthesize findings from ten moderate-quality studies involving 750 participants aged 10-20. These studies implemented SEM programs lasting 4 to 16 weeks, with one to five sessions per week. The analysis indicates significant improvements attributable to SEM, with effect sizes of 0.70 for content knowledge (p < 0.01), 0.70 for technical skills (p < 0.01), and 0.92 for game performance (p < 0.01). However, due to the moderate confidence in these results, caution is warranted in their interpretation. Subgroup analyses reveal that variations in student learning stages and game performance measurement methods, rather than intervention frequency and duration, influence the outcomes. Despite these encouraging results, further high-quality research across various sports is necessary to fully understand SEM's impact. Such research is essential for educators to effectively implement SEM and maximize its potential in educational contexts.